2008
DOI: 10.1002/jmri.21573
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation threshold comparison of time‐varying magnetic pulses with different waveforms

Abstract: Purpose: To clarify whether sinusoidal pulses possess lower thresholds than rectangular ones at perception threshold, a statement often made that contradicts the theory of stimulation. Materials and Methods:The results of a nerve stimulation study with 65 volunteers and with trapezoidal and sinusoidal gradient pulses were used to apply the combination of the electric field, induced in the tissue of the human body, with the "Fundamental Law of Electrostimulation." This law claims that the waveshape of a pulse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Equation (11) is therefore an accurate estimation for the fundamental law of magnetostimulation for frequencies in the kHz range and above. APPENDIX ACCURACY OF THE FUNDAMENTAL LAW OF MAGNETOSTIMULATION As explained in [40], the fundamental law of magnetostimulation given in (11) is not exact. This is because the relation given in (5) assumes that the E-field is larger than at all times , which is not true for an electric field generated by a sinusoidal magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Equation (11) is therefore an accurate estimation for the fundamental law of magnetostimulation for frequencies in the kHz range and above. APPENDIX ACCURACY OF THE FUNDAMENTAL LAW OF MAGNETOSTIMULATION As explained in [40], the fundamental law of magnetostimulation given in (11) is not exact. This is because the relation given in (5) assumes that the E-field is larger than at all times , which is not true for an electric field generated by a sinusoidal magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…must be based on the effective pulse duration. The result, then, is equal to the threshold of a rectangular pulse of equal duration . Taking simply the period of the haversine would reduce the averaged amplitude thereby suggesting that sinusoidal pulses are more efficient than rectangular pulses.…”
Section: Discussionmentioning
confidence: 97%
“…We believe that this theory can be extended to nonrectangular waveforms . The fundamental equation (FE4) demands that the “effective pulse duration” ends where the rheobase is reached.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is well documented that for a given peak B-field strength, the trapezoidal waveform has increased PNS thresholds compared to a sinusoidal waveform 50, 51 . Furthermore, it has been observed that the PNS thresholds increase linearly with the pulse duration (ramp rise-time) 3 .…”
Section: Methodsmentioning
confidence: 99%